Consultorio psicológico virtual: Una alternativa preventiva para la psicología - Guevara Castillo, Martha (2008)
Nowadays teres is an alternative to provide counseling and guidance through one of the easy-access mass media: Internet, since 2002, the virtual psychological office has given attention in order to help the user to find strategies for relieving his/her affective and emotional difficulties, clarifying doubts and finding alternatives to improve the quality of the file. The objetive is to help those people who for different reasons do not go directly to a psychologist´s office. The most frequent causes for consulting a psychologist are personality difficulties such as anxiety, depression, material conflicts, learning difficulties and compulsive gambling.